Evaluation of physico-chemical properties, fatty acid compositions and biodiesel characteristics of Brucea javanica and Hibiscus sabdariffa seed oils as sustainable biofuel / Khalilullah - Khalilullah, - (2018)
The biodiesel demand in worldwide is expected to rise sharply in the future because of its environmental friendly and renewable nature. Recently, biodiesel is mostly produced from edible feedstocks such as soybean, sunflower and palm oil. However, the competition of edible oil sources as food versus fuel makes edible oil not an ideal feedstock for biodiesel production. Biofuel production from non-edible plant seed oils is one of the effective way to anticipate the problems associated with fuel scarcity, food versus energy crisis and environmental pollution. In this study, exploration of the alternative non-edible feedstocks such as Brucea javanica seed oils (BJO) and Hibiscus sabdariffa seed oils (HSO) were investigated to be used for the production of biodiesel. Transesterification parameters such as methanol to oil ratio, temperature, catalyst and agitation were optimized by using Box-Behnken experimental design based on response surface methodology (RSM). The analysis of different oil properties, fuel properties and optimization of transesterification parameters for both feedstocks were investigated. The physicochemical properties of BJO investigated were found to be at the refractive index of 1.85, ultrasonic speed of 1.34 ms-1, acid value of 4.546 mg KOH/g, oxidative stability of 3 h according to the rancimat test and kinematic viscosity was of 17.428 mm2/s. On the other hand, HSO properties were refractive index of 2.16, ultrasonic speed of 1.52 ms-1, acid value of 5.486 mg KOH/g, oxidative stability of 3.48 h according to the rancimat test and the kinematic viscosity of 14.228 mm2/s. When converted into biodiesel using RSM experimental design, the optimum parameters found for converting Brucea javanica seed oils to biodiesel were 65 oC temperature, 1 % catalyst and 6:1 methanol to oil ratio with the highest yield of 94.34 %. In the case of Hibiscus sabdariffa seed oils, a methanol to oil ratio of 6:1, temperature 67.5 oC, catalyst 1% with a yield of 93.01 % were found to be the optimum parameters. The fuel properties of biodiesel produced were within the range of international standards such as EN14214 and ASTM standards of biodiesel except for the oxidative stability. To increase oxidative stability of the obtained biodiesel, the effectiveness of different antioxidants such as gallic acid (GA), tert-butyl-4-methylphenol (BHT), butylated hydroxyanisole (BHA), propyl gallate (PY) and t-butyl hydroquinone (TBHQ) were evaluated. All the antioxidants showed an improvement in the induction period of biodiesel with propyl gallate showing the highest efficiency in improving the oxidative stability of biodiesel up to 70 h. Both the feedstocks were successfully converted into biodiesel and a high biodiesel yield could be obtained using optimized transesterification parameters. Hence, it could be concluded in this study that non-edible feedstocks such as Brucea javanica and Hibiscus sabdariffa seed oils are suitable for biodiesel production that meets with the quality requirements of international standards as well as non-conflicting with food production.